2016
DOI: 10.1016/j.jsurg.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Declining Operative Experience for Junior-Level Residents: Is This an Unintended Consequence of Minimally Invasive Surgery?

Abstract: Introduction Our group has previously demonstrated an upward shift from junior to senior resident participation in common general surgery operations, traditionally performed by junior level residents. The objective of this study was to evaluate if this trend would correct over time. We hypothesized that junior resident case volume would improve. Methods A sample of essential laparoscopic and open general surgery procedures (appendectomy, inguinal herniorrhaphy, cholecystectomy, and partial colectomy) was cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…This is also confirmed by the fact that laparoscopic appendectomy is the surgery that showed the highest increase among surgeries by R3. This is similar to the findings by Mullen et al [ 11 ], reporting that, along with the proliferation of laparoscopy for common general surgical procedures, there has been a concomitant reduction in the participation of junior-level residents. With respect to surgical experience at both time points, it was confirmed that the R3 were most active.…”
Section: Discussionsupporting
confidence: 90%
“…This is also confirmed by the fact that laparoscopic appendectomy is the surgery that showed the highest increase among surgeries by R3. This is similar to the findings by Mullen et al [ 11 ], reporting that, along with the proliferation of laparoscopy for common general surgical procedures, there has been a concomitant reduction in the participation of junior-level residents. With respect to surgical experience at both time points, it was confirmed that the R3 were most active.…”
Section: Discussionsupporting
confidence: 90%
“…In Korea, this policy has been adopted for a balance between wellness and proper training experience among residents since the end of 2015. However, there are some concerns, such as the negative effects due to significant reduction in case volume and inadequate training experience 1 9 10. Swide and colleagues reported that work-hour restriction improves resident’s wellness, but improvement in patient safety or residents’ quality of education remained unclear based on a survey conducted by the US anesthesiology residency program 11.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the variation in educational environments and each specialty’s characteristics, changes to the educational programs will be needed in the future 14. To provide better opportunities for learning interventional techniques, alternative training methods, including simulation program, bench models, virtual tools, phantom models and live animal models will be needed to improve basic skills 1 15–20. In addition, we suggest that the current PM training goal be changed to reflect the residents’ opinions of low interventional opportunity and more ultrasound block learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations